Analyzing various approaches for Measurement of Solar PV Potential through Urban Built Form Geometry modifications - Chatterje, Shambhabi; Ghosh, Kamalika; Das, Debashish (International Journal of Computer Sciences and Engineering, 2025)
In India fossil fuel are depleting fast due to ever rising population, over-exploitation, besides increasing the environmental cost. Conventional thermal power has some demerits due to the depletion of recourses, pollution, etc. Society is shifting from agricultural to Industrial / Commercial based , with modern lifestyle which leads to urbanization .Since land area is fixed multistoried buildings are growing fast. The demand for electrical energy is also increasing rapidly. This calls for other form of energy generation, especially through renewable resources. India is privileged with its geographical position closed to equator and has almost 300 days with 10hours solar irradiance with average value of 1335W/m2. So the urban planning with utilization of solar panels need to be incorporated together to reduce energy consumption and save fuel for the future generations. This huge amount of solar resource potential gets wasted which can be utilized by urban built form geometry modifications taking the building shape and density aspects and implementing solar panels on the roof of the buildings also. The design need to be done in a way so that maximum solar potential can be utilized and shadows due to other buildings are avoided. The main aim of this research work is to analyze various methods for calculating the solar PV potential and measure the potential of solar photovoltaic capacity..